Performance comparison of liquid smokes from galam wood, rubber wood, and oil palm frond as latex coagulants on the quality aspects of the rubber cup lump - Nugroho, Ph.D., Agung; Majid, Iqbal Maulana; Al Hakim, Hisyam Musthafa (Jurnal Riset Industri Hasil Hutan, 2019)
The quality of rubber cup lump is ditermined by several factors, one of them is the latex coagulant. The type of latex coagulant also affects the coagulating time. Liquid smoke is one of the most recommended latex coagulants due its save and effective operation. Deorub, the most popular liquid smoke, is made from shell of oil palm kernel. There are still many alternatives of liquid smoke materials that may have lower economic values. This study was aimed to evaluate and compare the performance of three liquid smokes produced from three alternative materials namely galam wood, rubber wood, and oil palm frond as latex coagulants. This study was performed using groups random design with two factors, namely type of coagulants and the concentrations (10% and 5%). Evalution was performed on the speed of coagulating time and also the quality of rubber cup lumps resulted by the tested coagulants, such as water content, rubber dry weight, ash content, and also the value of sensory quality (smell, color, texture, and the bubble). Liquid smoke resulted from oil palm fronds showed the best performance due to it’s lowest pH value (2.5) and the shorthest coagulating time (40 min) at concentration of 10%, which produced rubber lumps with rubber dry weight of 99.86% and ash content of 0.83%. Meanwhile, the highest yield of liquid smoke was resulted from galam wood (10%) with coagulating time of 72 minutes.